Giacomo Meyerbeer : Jephtas Gelübde (Jephtha's Vow) - Vocal/Piano Score - Letellier, Robert Ignatius; Starr, Mark (Cambridge Scholars Publishing, 2013)
Meyerbeer's first opera, Jephtas Gelübde, has a libretto by the German academic Alois Schreiber, based on a Biblical theme taken from chapters 11-12 of the Book of Judges. The story centres on the vow the ancient Israelite Judge made to God in return for victory over the enemy: ""If thou wilt give the Ammonites into my hand, then whatever comes forth from the doors of my house to meet me, when I return victorious . . . I will offer him up for a burnt offering"". The first person he was fatefull...
Keywords: Meyerbeer, Giacomo, : 1791-1864; Jephthah : (Biblical judge); Operas : Scores; Operas : Librettos